Association Between Vestibular/Ocular Motor Screening (VOMS) and Concussion Recovery Time in Collegiate Participants. (26th July 2019) - Petit, K M; Anderson, M; Bretzin, A C; Tomczyk, C P; Savage, J L; Covassin, T
Abstract: Purpose: To evaluate the relationship between Vestibular/Ocular Motor Screening (VOMS) change scores and total scores with recovery time after a concussion in collegiate participants. Methods: Participants completed the VOMS within 72 hours of concussion diagnosis. The VOMS consists of smooth pursuits, horizontal saccades, vertical saccades, near-point convergence (NPC), horizontal vestibular ocular reflex (VOR), vertical VOR, and visual motions sensitivity (VMS). Prior to the VOMS, athletes rate pre-provocation symptoms for headache, dizziness, nausea and fogginess, and again after each VOMS component on a scale from 0 (none) to 10 (severe) to obtain a total provocation score for each component. Change scores were calculated by subtracting total pre-provocation symptoms from total provocation for each component. Recovery time was defined as the number of days from injury to physician clearance. A Spearman's rank correlation assessed relationships between recovery time and VOMS outcomes. Results: Seventy-six participants (47 male, 29 female; 18.6±2.2 years old) completed the VOMS and took 13.5±5.4 days to recover. Total provocation scores for each VOMS component were associated with recovery time (smooth pursuits r=.36, p<.001; horizontal saccades r=.40, p<.001; vertical saccades r=.40, p<.001; NPC r=.40, p<.001; horizontal VOR r=.38, p=.001; vertical VOR rs=.31, p=.01; VMS rs=.38, p=.001). Only horizontal saccades (r=.37, p=.001), vertical saccades (r=.30, p=.01), and NPC (r=.27, p=.02) change scores were associated with recovery time. Conclusion: VOMS total symptom provocation and change scores for vertical saccades, horizontal saccades, and convergence may provide insight into concussion recovery length. Future research should assess the utility of VOMS change scores when evaluating for a concussion.